In Vitro Free Radical Scavenging Properties and Anti-Inflammatory Activity of Ilex paraguariensis (Maté) and the Ability of Its Major Chemical Markers to Inhibit the Production of Proinflammatory Mediators - Ingrid Vicente Farias; Eduarda Fratoni; Lais Cristina Theindl; Angela Machado de Campos; Eduardo Monguilhott Dalmarco; Flavio Henrique Reginatto (Mediators of Inflammation)
Ilex paraguariensis A. St. Hil. (Aquifoliaceae), popularly known as “yerba mate,” has great economic and social significance for the population of Southern Latin America. This study was conducted (1) to investigate the phytochemical composition of four different standardized extracts, (2) to investigate its free radical scavenging properties, and (3) to investigate the anti-inflammatory action of I. paraguariensis and its major chemical markers. The chemical profile was achieved by Folin-Ciocalteu, by LC/DAD, and by LC/MS assays, while the antioxidant and anti-inflammatory properties were investigated, respectively, by DPPH assay and by inhibition of nitric oxide (Griess reaction) and TNF-α (ELISA). Our results demonstrated that the IA (aqueous infusion extract) showed higher amounts of total phenolic contents (266.62±10.85 mg CAE·g-1 DE), the highest amounts of all six chemical markers (theobromine, 5-O-caffeoylquinic acid, 4-O-caffeoylquinic acid, 3-O-caffeoylquinic acid, caffeine, and rutin), and stronger antioxidant activity (EC50=54.4±5.14 μg·mL−1). The IA extract also showed the lowest inhibition of NOx secretion (50.10±8.97%) as well as inhibition of TNF-α (83.33±4.01%). Regarding the chemical markers, all compounds showed strong inhibition of NOx secretion, especially theobromine, which was 200x more potent than dexamethasone. Furthermore, TNF-α secretion was also significantly decreased by THEO at 0.033 μM (22.15±6.49%), NCA at 1.97 μM (27.46±3.98%), CCA at 0.35 μM (39.76±5.73%), CGA at 0.56 μM (23.58±5.79%), CAF at 0.52 μM (26.45±5.34%), and RUT at 0.16 μM (40.18±3.70%). Our results suggest that I. paraguariensis and its major chemical markers have strong free radical scavenging properties as well as showed important anti-inflammatory activity and that these compounds in a plant extract may work based on several different mechanisms synergistically, resulting in moderating the immune system.